Variational analysis of the Ryanodine Receptor 2 gene in cases of sudden unexpected death in the young and infants admitted to Pretoria Medico-Legal Laboratory - Van Niekerk, Chantal (University of Pretoria, 2020)
Dissertation (MSc (Chemical Pathology))--University of Pretoria, 2019.